2009
DOI: 10.3390/ijerph6102639
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Weather Conditions on Physical Activity Participation Using Objective Measures

Abstract: Habitual physical activity is an important determinant of health, yet many people are considered to be inactive. Identification of the obstacles to greater participation is necessary for the development of strategies to overcome those obstacles. The weather has been identified as a perceived barrier to participation in physical activity, but exactly which adverse weather conditions are most important, and the extent to which they contribute to decreases in physical activity have rarely been quantified in popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
154
6
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(168 citation statements)
references
References 51 publications
6
154
6
2
Order By: Relevance
“…The first point that the current literature failed to consider is the effect of ambient temperature and humidity on occupant behavior in commercial buildings. Occupancy energy-use behavior varies according to weather conditions [73,150]. Individual occupant's behaviors may have a larger impact on energy consumption in hot-dry climates than in mild-humid ones [8].…”
Section: Overview Of Current Approachesmentioning
confidence: 99%
“…The first point that the current literature failed to consider is the effect of ambient temperature and humidity on occupant behavior in commercial buildings. Occupancy energy-use behavior varies according to weather conditions [73,150]. Individual occupant's behaviors may have a larger impact on energy consumption in hot-dry climates than in mild-humid ones [8].…”
Section: Overview Of Current Approachesmentioning
confidence: 99%
“…Furthermore, a study consisting of 41 older Japanese people (above 70 years) revealed that the number of steps taken per day decreased with increasing precipitation 23 , as well as for another study 7 . We could not confirm that precipitation was the most influential on PA of all the weather variables, as suggested previously 10 , because different influences were found for each age and gender group.…”
Section: Discussionmentioning
confidence: 57%
“…A review by Chan et al 10 focused on the effects of weather conditions on PA and categorised studies into two groups: studies that used season as a weather indicator and studies that objectively measured climatological conditions. Of the 24 studies reviewed, 16 used season as a climate indicator, and the other 8 examined the effects of weather (isolated weather indicators) on PA.…”
Section: Introductionmentioning
confidence: 99%
“…Drawing on the computation method, some scholars have reported a significant association between apparent temperature and outdoor activity, such as taking an outdoor walk (e.g. Chan & Ryan, 2009). However, few studies have examined the impact of this heat stress index on travel by public transport.…”
Section: Datamentioning
confidence: 99%